Management of steep land - Verma, G P; Singh, Y P; Singh, Anil Kumar (Indian Farming, 2018)
Steep land is classed as unsuitable for arable farming under the Land Capability Classification, as it usually has shallow soil severely eroded by rainwater, impoverished of plantnutrients and soil colloids. Still such land is brought under the plough even in advanced countries like U.S.A. and Canada. But no intensive research on management of such land has been conducted and consequently fool proof technology for appropriate management of steep land is not available. Hence, the need for intensive research on steep land management cannot be over emphasized. Various aspects to be covered are: land and water management practices, nature and density of vegetative cover, negotiation of slope, run-off collection and recycling and alternate land-use systems.